2012
DOI: 10.1292/jvms.11-0319
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multiplex PCR and PCR-RFLP Method for Serotyping of Avibacterium paragallinarum

Abstract: ABSTRACT. Avibacterium (Haemophilus) paragallinarum (A. paragallinarum) is a causative agent of infectious coryza in chickens and is classified into three serovars by agglutination tests. In an effort to identify the serovars easily, PCR and PCR-RFLP were employed. As the target gene for PCR, the hypervariable region of HMTp210, which encodes the HA antigen, was used. PCR using primer sets around the hypervariable region amplified 0.8, 1.1 and 1.6 kbp fragments for serovars A, B and C, respectively. Alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
49
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 11 publications
1
49
1
2
Order By: Relevance
“…17 It is known that a region within the HMTp210 gene (termed region 2), shows, on the basis of a limited data set, sequence diversity between Page serogroups, a diversity that has been exploited in the proposed PCR. 15 In the current study, this proposed PCR alternative to conventional serotyping has been evaluated with the full set of Page and Kume reference strains as well a number of diverse Av. paragallinarum field isolates.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…17 It is known that a region within the HMTp210 gene (termed region 2), shows, on the basis of a limited data set, sequence diversity between Page serogroups, a diversity that has been exploited in the proposed PCR. 15 In the current study, this proposed PCR alternative to conventional serotyping has been evaluated with the full set of Page and Kume reference strains as well a number of diverse Av. paragallinarum field isolates.…”
mentioning
confidence: 99%
“…12 All reference strains and field isolates included in the study were examined by a serotyping mPCR as reported. 15 Briefly, the genomic DNA was extracted by using a commercial kit, a according to the manufacturer's instructions. The PCR reactions were performed in a total volume of 25 μl containing 2.5 μl of 10× PCR buffer included in the kit, b 0.2 mM of each deoxyribonucleotide triphosphate, 0.2 μM of each Page serovar-specific primer: ABC forward 5′-GGCTCACAGCTTTATGCAA CGAA-3′; A reverse 5′-CGCGGGATTGTTGATTTTGT T-3′; B reverse 5′-GGTGAATTTCACCACACCAC-3′; and C reverse 5′-TAATTTTCTTATTCCCAGCATCAATA CCAT-3′.…”
mentioning
confidence: 99%
See 3 more Smart Citations